Reply to Urbina, F.; Benavides, A. Telangiectatic Mastocytosis: If It Is Not Mastocytosis, What Is It? Comment on “Brockow et al. Challenges in the Diagnosis of Cutaneous Mastocytosis. Diagnostics 2024, 14, 161” - Knut Brockow; Rebekka Karolin Bent; Simon Schneider; Sophie Spies; Katja Kranen; Benedikt Hindelang; Zsuzsanna Kurgyis; Sigurd Broesby-Olsen; Tilo Biedermann; Clive E. Grattan (Diagnostics)
We appreciate the interest and reflections of Urbina and Benavides on our recent article published in Diagnostics and presentation of their two new patients [...]